2006
DOI: 10.1158/1535-7163.mct-06-0339
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ABCG2 drug transporter in the resistance and oral bioavailability of a potent cyclin-dependent kinase/Aurora kinase inhibitor

Abstract: Cell cycle kinase inhibitors have advanced into clinical trials in oncology. One such molecule, JNJ-7706621, is a broad-spectrum inhibitor of the cyclin-dependent kinases and Aurora kinases that mediate G 2 -M arrest and inhibits tumor growth in xenograft models. To determine the putative mechanisms of resistance to JNJ-7706621 that might be encountered in the clinic, the human epithelial cervical carcinoma cell line (HeLa) was exposed to incrementally increasing concentrations of JNJ-7706621. The resulting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…32 For example, BCRP was shown to confer resistance to the cyclin-dependent kinase and Aurora kinase inhibitor, JNJ-7706621, in cells propagated in the presence of the drug. 33 Interestingly, both BCRP expression and resistance to JNJ-7706621 were fully reversed following drug withdrawal, 33 indicating that BRCP-mediated resistance does not require a genomic alteration. Activation of nuclear hormone receptors 34 and promoter methylation 35 have been demonstrated to control the transcription of BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…32 For example, BCRP was shown to confer resistance to the cyclin-dependent kinase and Aurora kinase inhibitor, JNJ-7706621, in cells propagated in the presence of the drug. 33 Interestingly, both BCRP expression and resistance to JNJ-7706621 were fully reversed following drug withdrawal, 33 indicating that BRCP-mediated resistance does not require a genomic alteration. Activation of nuclear hormone receptors 34 and promoter methylation 35 have been demonstrated to control the transcription of BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…ABCG2 mRNA expression was higher compared to other efflux transporter in the human small intestine, which is a rate-limiting barrier to oral drug absorption [64] . The important impact of ABCG2 on the intestinal absorption was further supported by several knockout mice research, which have indicated that ABCG2 affects the pharmacological and toxicological behavior of many drugs [65][66][67] . Also, polymorphisms might influence the role of ABCG2 in intestinal absorption.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 89%
“…Several researchers have reported high levels of ABCG2 in the digestive tract (47), suggesting a role for ABCG2 in the oral bioavailability of substrate drugs. This has been reported even for drugs currently in clinical development (48). To increase oral bioavailability, coadministration of ABCG2 substrate drugs with ABCG2 inhibitors has been suggested.…”
Section: Discussionmentioning
confidence: 99%